2020
DOI: 10.1186/s12891-020-03277-3
|View full text |Cite|
|
Sign up to set email alerts
|

Screw fixation in stemless shoulder arthroplasty for the treatment of primary osteoarthritis leads to less osteolysis when compared to impaction fixation

Abstract: Background Stemless total shoulder arthroplasty is a well-established and reliable surgical treatment option for glenohumeral osteoarthritis resulting in loss of pain and improvement of shoulder function. Currently the two methods for the fixation of the humeral component are either screw fixation or impaction. The purpose of this study is the clinical and radiological comparison of two different stemless designs (screw fixation vs impaction) for total shoulder arthroplasties in patients suffering from primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A study by Alikhah et al has shown that stemless shoulder arthroplasty implants relying on either “press-fit” impaction or screw fixation techniques have been shown to share similar results in terms of clinical and radiographic outcomes. 2 Although medial calcar resorption was documented at a higher rate in patients with the impaction-fitted prosthesis, there were no significant differences in clinical function when compared with patients who were treated with a screw fixation designs. 2 The authors hypothesized that impaction-fitted implants are more prone to medial calcar resorption, whereas the screw fixation prosthesis permits a better load distribution due to its baseplate and constant rim load.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study by Alikhah et al has shown that stemless shoulder arthroplasty implants relying on either “press-fit” impaction or screw fixation techniques have been shown to share similar results in terms of clinical and radiographic outcomes. 2 Although medial calcar resorption was documented at a higher rate in patients with the impaction-fitted prosthesis, there were no significant differences in clinical function when compared with patients who were treated with a screw fixation designs. 2 The authors hypothesized that impaction-fitted implants are more prone to medial calcar resorption, whereas the screw fixation prosthesis permits a better load distribution due to its baseplate and constant rim load.…”
Section: Discussionmentioning
confidence: 80%
“… 2 Although medial calcar resorption was documented at a higher rate in patients with the impaction-fitted prosthesis, there were no significant differences in clinical function when compared with patients who were treated with a screw fixation designs. 2 The authors hypothesized that impaction-fitted implants are more prone to medial calcar resorption, whereas the screw fixation prosthesis permits a better load distribution due to its baseplate and constant rim load. Further theories suggest that particles from the breakdown of polyethylene may be responsible for the occurrence of “humeral notching” 33 when there is impingement of the medial calcar against the glenoid component.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, Akilhah et al compared a hollow screw design to the impaction type design used in this study and demonstrated that the hollow screw with a trunnion may prevent and be protective of medical calcar bone resorption. 22 Proximal stress shielding may also occur when there is distal contact of the implant with the inner aspect of the lateral cortex. This leads to proximal bone adaptations as the loads are transmitted from the metallic humeral head, thru the stemless implant, and preferentially exit the implant distally at the contact location with the inner cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Akilhah et al compared a hollow screw design to the impaction type design used in this study and demonstrated that the hollow screw with a trunnion may prevent and be protective of medical calcar bone resorption. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Based on work by Habermeyer et al and Krukenberg et al, there does not appear to be a difference in terms of humeral loosening (n = 0 in both designs), humeral osteophytic exostosis (n = 0 in both designs), or functional outcomes [ 8 , 9 ]. Radiographic medial calcar resorption occurs more often with the impaction design, but there does not appear to be a clinical implication of this, as both designs result in significantly improved Constant and Subjective Shoulder Value (SSV) scores [ 8 , 10 ].…”
Section: New Perspectives and Innovations In Anatomic Shoulder Arthro...mentioning
confidence: 99%